Using Quantum Teaching to Improve Mathematics Learning Outcomes in Junior High School: A Classroom Action Research Approach - Rini Fitriyana; Astri Setyawati; Siti Lestari; Djatmiko (Journal of Transdisiplinary Studies in Education, 2025)
Background: At SMP Negeri 1 Kotagajah, student performance in mathematics was found to be below the required Kriteria Ketuntasan Minimal (KKM). This study explores how the Quantum Teaching model can be implemented to improve students' learning outcomes, particularly in exponentiation.Aims: This research aims to assess the impact of the Quantum Teaching model on enhancing the mathematics achievement of eighth-grade students at SMP Negeri 1 Kotagajah for the 2023/2024 academic year.Methods: A Classroom Action Research (CAR) methodology was used in this study, conducted in two cycles. Each cycle consisted of planning, implementation, observation, and reflection. Data was gathered through tests, interviews, observations, and documentation, with a focus on students' mathematics performance, especially in the topic of exponentiation.Results: The study found notable improvements in student achievement. In the first cycle, 66% of students met the learning objectives, while in the second cycle, this increased to 97%. The application of the Quantum Teaching model led to higher levels of student participation and a deeper understanding of the material.Conclusion: The study indicates that the Quantum Teaching model is an effective strategy for improving mathematics learning outcomes. It fosters a more engaging and interactive classroom environment, enhancing student performance in mathematics at the junior high school level.